If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + x + -3 = 6x + 6 Reorder the terms: -3 + 6x + x = 6x + 6 Combine like terms: 6x + x = 7x -3 + 7x = 6x + 6 Reorder the terms: -3 + 7x = 6 + 6x Solving -3 + 7x = 6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + 7x + -6x = 6 + 6x + -6x Combine like terms: 7x + -6x = 1x -3 + 1x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + 1x = 6 + 0 -3 + 1x = 6 Add '3' to each side of the equation. -3 + 3 + 1x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 6 + 3 1x = 6 + 3 Combine like terms: 6 + 3 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| 4x+2x+x=-7 | | 7x+5(4x-39)=-6 | | x^2-41x-540=0 | | 36x+4y=32 | | .36(18)+0.06x=0.12(24+x) | | 107=56-6(x-10) | | 60x+11y=30 | | 3+6x=13+16x | | 6y-4=5-8y | | 6*x-17=7 | | 4t+b=q | | 6*x-10=7 | | -7(-9x-29)=1274 | | 36=x(12-3) | | 6y-20y= | | 9(m+2)=9m+18 | | 4r^2+11r+6=0 | | -5x+4=-40 | | 1.07/x=15/100 | | D=x(f-d) | | f(x)=cos^5x | | tanx=0.2 | | 5-[-2]= | | x^4-6x^3-9x^2-54x-162=0 | | 5(x-8)=-42+5x | | 3y^2+3y+6=0 | | 2(n-8)-n=n-16 | | 7b^2+29b-30=0 | | -112=-27-5x | | -4(6a-2)= | | 90(x+24)+90(x)=4x(x+4) | | 14.5y=6 |